1993
DOI: 10.1029/93gl01596
|View full text |Cite
|
Sign up to set email alerts
|

Correlation dimension and affinity of AE data and bicolored noise

Abstract: We have made a detailed analysis of several periods of the AE time series and find that the average correlation dimension is 3.4. We have generated bicolored noise and shown that it shares many properties with the AE data. We also find that the AE time series is self‐affine such that the affinity exponent changes on a time scale of about two hours, which is a typical length of magnetospheric substorms. We suggest that this same time scale appears as a spectral break at about 5.6 × 10−5Hz (5‐hour period) in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 20 publications
9
70
0
Order By: Relevance
“…It is reasonable to assume that the large-amplitude fluctuations are produced by internal bursts and the externally driven fluctuations contribute mostly to the small amplitude portion. Takalo et al (1993) have estimated the correlation dimension of AE index as 3.4 and reported that bicoloured noise shares many properties with AE index. It is believed that the stochastic nature of the AE index fluctuations is of internal, and not of external origin (Burlaga, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…It is reasonable to assume that the large-amplitude fluctuations are produced by internal bursts and the externally driven fluctuations contribute mostly to the small amplitude portion. Takalo et al (1993) have estimated the correlation dimension of AE index as 3.4 and reported that bicoloured noise shares many properties with AE index. It is believed that the stochastic nature of the AE index fluctuations is of internal, and not of external origin (Burlaga, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…a measure of fluctuations with no characteristic scales (power law), over a wide range of scales. Examples include (a) power spectra of ground magnetic fields (Cambell, 1976;Francia et al, 1995;Consolini et al, 1998;Weatherwax et al, 2000;Abel and Freeman, 2002), and ionospheric electric fields (Kintner, 1976;Weimer et al, 1985;Bering et al, 1995;Buchert et al, 1999;Abel and Freeman, 2002;Golovchanskaya et al, 2006), (b) probability density functions (PDFs) of durations between threshold crossings of the auroral electrojet indices AU and AL (Freeman et al, 2000), (c) PDFs of durations, areas, and other quantities of auroral bright patches (Lui et al, 2000;Uritsky et al, 2002;Kozelov et al, 2004) and (d) structure functions of the auroral electrojet indices AU, AL and AE, the polar cap index PC (Takalo et al, 1993;Takalo and Timonen, 1998;Hnat et al, 2002), ground magnetic fields (Pulkkinen et al, 2006) and ionospheric convection (Parkinson, 2006;Abel et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…So far, evidence to support this is based on the observation of (a) intermittent energy transport in the magnetotail -"bursty bulk flow events" [Angelopoulos et al, 1992], (b) magnetotail turbulence [Hoshino, 1994;Borovsky, 1997], (c) the apparent low dimensionality [Sharma, 1995;Klimas, 1996] of the Auroral Electrojet (AE) indices [Davis and $ugJura, 1966], and (d) scale-free properties of the AE indices including a "l/f" region in the power spectrum [Tsurutani et al, 1990], self-affinity [Takalo et al, 1993], and power law distributions of the lifetimes [Takalo, 1993;Consolini, 1999;Takalo, 1999] and energies [Consolini, 1997;Consolini, 1999] of burst events. Burst lifetime probability densities …”
Section: Introductionmentioning
confidence: 99%